2009
DOI: 10.1088/0022-3727/42/19/194014
|View full text |Cite
|
Sign up to set email alerts
|

Review of profile and roughening simulation in microelectronics plasma etching

Abstract: Plasma etching of thin films is essential for microelectronics manufacturing. With current feature sizes of 35 nm in production and processes for smaller devices being developed, the sidewall roughness is within the order of magnitude of the gate length of the device, and therefore significantly impacts the devices' performance. In this paper we review the modelling of the surface profile evolution in plasma etching. Both two-dimensional (2D) and three-dimensional (3D) models have been developed using a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 113 publications
3
47
0
Order By: Relevance
“…They both show an anisotropic morphology of the sidewall roughness after the lithography step which is accentuated during the subsequent plasma etching steps because of the directionality of the ion flux. 16 This observation is in full agreement with a previous study. 17 However, while X-SEM gives good qualitative analyses of roughness, the developed AFM technique can also be used to obtain a quantitative estimation of the roughness and to calculate the LER all along the pattern height after each plasma etching step involved in the patterning as shown in Figure 6(b).…”
Section: A Transfer Into a Silicon Gate Stacksupporting
confidence: 93%
“…They both show an anisotropic morphology of the sidewall roughness after the lithography step which is accentuated during the subsequent plasma etching steps because of the directionality of the ion flux. 16 This observation is in full agreement with a previous study. 17 However, while X-SEM gives good qualitative analyses of roughness, the developed AFM technique can also be used to obtain a quantitative estimation of the roughness and to calculate the LER all along the pattern height after each plasma etching step involved in the patterning as shown in Figure 6(b).…”
Section: A Transfer Into a Silicon Gate Stacksupporting
confidence: 93%
“…Surface roughness of polymeric substrates is important not only in micro-and nanoelectronics {e.g., line edge roughness (LER) issue [1][2][3] }, but also for several applications in other fields. For example, it affects wetting and optical properties of surfaces, [4,5] the adsorption of proteins on surfaces, [6,7] and the cell adhesion and growth.…”
Section: Introductionmentioning
confidence: 99%
“…a model which includes the effect of impurities or etch-inhibitors or depositing particles for the explanation of pattern formation during IBS of Si was pinpointed by Macko et al in a recent work [14]. There are interesting modeling works with focus on surface roughness and pattern formation which refer either to etching only [22][23][24][25] or deposition only [26,27]. A first effort to model SIMED with a (1+1)d stochastic modeling framework was reported in [28], where it was shown that SIMED could lead to an instability in roughness evolution versus time (linear increase of root mean square of roughness versus time) and dual scale surface roughness.…”
Section: Introductionmentioning
confidence: 99%